An annotated list of the Opostegidae of the Himalaya, with a description of Pseudopostega brevicaudata sp. nov. (Lepidoptera: Nepticuloidea) - Stonis, Jonas Rimantas; Remeikis, Andrius; Sruoga, Virginijus (Zootaxa, 2013)
Seven species of Opostegidae are reported from the Himalaya:Opostegoides pelorrhoa (Meyrick, 1915), Pseudopostega frigida (Meyrick, 1906), P. nepalensis Puplesis & Robinson, 1999, P. zelopa (Meyrick, 1905), Pseudopostega brevicaudata Remeikis & Stonis, sp. nov., Opostega chalcophylla Meyrick, 1910 and one documented but left unnamed Opostegoides species. Genital structures of all species treated herein are illustrated with photographs for the first time.